Analisis Pertimbangan Hakim dalam Menjatuhkan Pidana Percobaan terhadap Pelaku tindak Pidana Pemberian Keterangan Palsu di Atas Sumpah: (Studi Putusan Nomor: 1353/Pid.B/2017/PN.Tjk dan 23/Pid/2018/PT.TJK) - Akbar, Muhammad; Dewi, Erna; Fardiansyah, Ahmad Irzal (LPPM Institut Pendidikan Nusantara Global, 2025)
One of the criminal acts that frequently occurs in society is giving false testimony under oath, which is punishable by imprisonment; however, in practice, judges may impose a suspended sentence. This study aims to analyze the judge’s considerations in imposing a suspended sentence on perpetrators of giving false testimony under oath and its conformity with the objectives of punishment. The research employed normative legal research with statutory and conceptual approaches. The data used were secondary data obtained through library research and analyzed descriptively and qualitatively. The findings show that in Decision Number 1353/Pid.B/2017/PN.Tjk and 23/Pid/2018/PT.Tjk, the juridical consideration of the judges was based on the fact that the defendant was proven to have violated Article 242 paragraph (1) of the Indonesian Criminal Code. The philosophical consideration was directed at efforts to rehabilitate the defendant so that he would not repeat the offense, while the sociological consideration involved taking into account both mitigating and aggravating factors. The imposition of the suspended sentence was deemed consistent with the objectives of punishment, particularly given the defendant’s advanced age (68 years) and in line with the relative theory, which emphasizes punishment as a means of learning rather than mere retribution.